Antioxidant Activity of Selected Natural Medicines used in Nepal - Baral, KP; Basnet, P (Journal of Chitwan Medical College, 2013)
Diminished antioxidant defence or increased production of reactive oxygen and nitrogen species in the biological system can result into oxidative stress which can cause damage to deoxyribonucleic acid (DNA), proteins, lipids and as a result different disease states arise like cancer, neurodegenerative diseases, rheumatoid arthritis. Antioxidants from different plant resources can significantly delay or prevent oxidation of the substrate and hence prevents from various diseases. Therefore, present research was focused in search of potent natural antioxidants. For the study, methanolic extracts of twenty-five common natural medicines, mostly spices were screened using 1,1–diphenyl–2–picrylhydrazyl (DPPH) radical for their antioxidative activities. Among them, extracts of Chebulae Fructus, Terminalia Billericae Fructus, Phyllanthi Fructus, Cinnamomi Cortex, Arecae Semen, Pericarpium Punicae Granati, Syzygiae Fructus, Rhei Rhizoma, Pterocarpi Lignum and Santali Lignum Albi showed potent antioxidative activity with EC50 values being 1.5, 2.1, 1.4, 2, 1.5, 1.45, 2.7, 2.9, 3, 3.8 μg/mL, respectively. Ascorbic acid (EC50: 2.6 μg/mL) was used as positive control. Therefore, consumers can increase their intake of foods rich in antioxidant compounds that can lower the risk of chronic health problems DOI: http://dx.doi.org/10.3126/jcmc.v3i2.8439 Journal of Chitwan Medical College Vol.3(2) 2013 27-31